Treatment Selection and Survival Outcomes in Locally Advanced Proximal Gastric Cancer: A National Cancer Data Base Analysis - Tang, Song; Liu, Fangfang; Li, Yumin; Zhao, Lulu; Wang, Xiang; Khan, Sajid A.; Chen, Yingtai; Zhang, Yawei (Frontiers in Oncology, 2020)
Background: We aimed to assess long-term survival between locally advanced proximal gastric cancer (LAPGC) patients who underwent proximal gastrectomy (PG) and those who underwent total gastrectomy (TG) to evaluate the optimal extent of resection and adjuvant therapy. Materials and methods: Patients diagnosed with locally advanced proximal gastric adenocarcinoma were selected from the National Cancer Data Base (2004-2015) in America. Survival analysis was performed via Kaplan-Meier and Cox proportional hazards models. Results: A total of 4,381 eligible patients were identified, 1,243 underwent PG and 3,138 underwent TG. Patients in TG group had a poor prognosis (hazard ratio [HR] = 1.13, 95% confidence interval [CI]: 1.03-1.25) compared with those in PG group. Moreover, postoperative chemoradiation therapy was associated with improved overall survival compared to surgery alone (HR =0.71, 95% CI: 0.53-0.97) in LAPGC patients who had PG, while preoperative chemotherapy (HR =0.74, 95% CI: 0.59-0.92) was associated with improved survival among patients who had TG. Conclusions: Our study suggested that LAPGC patients underwent PG experienced better long-term outcomes than those underwent TG. It also suggested that multimodality treatment of LAPGC, including preoperative chemotherapy followed by TG or postoperative chemotherapy followed by PG, should be considered to achieve better long-term outcomes.